Cost-Effectiveness Analysis of Stereotactic Ablative Body Radiation Therapy Compared With Surgery and Radiofrequency Ablation in Two Patient Cohorts: Metastatic Liver Cancer and Hepatocellular Carcinoma. Issue 3 (March 2021) - Jin, H.; Chalkidou, A.; Hawkins, M.; Summers, J.; Eddy, S.; Peacock, J.L.; Coker, B.; Kartha, M.R.; Good, J.; Pennington, M.; Baker, A.; et al.
Abstract: Aims: To compare the cost-effectiveness of stereotactic ablative body radiation therapy (SABR) with radiofrequency ablation and surgery in adult patients with metastatic liver cancer and hepatocellular carcinoma (HCC). Materials and methods: Two patient cohorts were assessed: liver oligometastases and HCC. For each patient cohort, a decision analytic model was constructed to assess the cost-effectiveness of interventions over a 5-year horizon. A Markov process was embedded in the decision model to simulate the possible prognosis of cancer. Data on transition probabilities, survival, side-effects, quality of life and costs were obtained from published sources and the SABR Commissioning through Evaluation (CtE) scheme. The primary outcome was the incremental cost-effectiveness ratio with respect to quality-adjusted life-years. The robustness of the results was examined in a sensitivity analysis. Analyses were conducted from a National Health Service and Personal Social Services perspective. Results: In the base case analysis, which assumed that all three interventions were associated with the same cancer progression rates and mortality rates, SABR was the most cost-effective intervention for both patient cohorts. This conclusion was sensitive to the cancer progression rate, mortality rate and cost of interventions. Assuming a willingness-to-pay threshold of £20 000 per quality-adjusted life-year, the probability that SABR is cost-effective was 57% and 50% in liver oligometastases and HCC, respectively. Conclusions: Our results indicate a potential for SABR to be cost-effective for patients with liver oligometastases and HCC. This finding supports further investigation in clinical trials directly comparing SABR with surgery and radiofrequency ablation. Highlights: The first economic analysis which compares the cost-effectiveness of surgery, radiofrequency ablation (RFA) and stereotactic body radiation therapy (SABR) for people with liver oligometastases and hepatocellular carcinoma. For patients treated with SABR who can achieve similar mortality and cancer progression rates to those treated with surgery or RFA, SABR is most cost-effective. For patients who might be able to achieve better cancer progression control and/or additional survival benefits from surgery or RFA compared to SABR, surgery or RFA is most cost-effective.